Co-composting of sewage sludge as an effective technology for the production of substrates with reduced content of pharmaceutical residues - Vráblová, Martina; Smutná, Kateřina; Chamrádová, Kateřina; Vrábl, Daniel; Koutník, Ivan; Rusín, Jiří; Bouchalová, Markéta; Gavlová, Anna; Sezimová, Hana; Navrátil, Martin; Chalupa, Richard; Tenklová, Barbora; et al. (The Science of the total environment, 2024)
Sewage sludge is a valuable source of elements such as phosphorus and nitrogen. At the same time, heavy metals, emerging organic compounds, micropollutants (pharmaceuticals, pesticides, PCPs, microplastics), or some potentially dangerous bacteria can be present. In this study, the sewage sludge was aerobically treated by composting with other materials (co-composted), and the resulting substrate was tested for suitability of its use in agriculture. Closer attention was focused on the pharmaceuticals (non-steroidal antiphlogistics, sartanes, antiepileptics, caffeine, and nicotine metabolites) content and ecotoxicity of the resulting substrates in the individual phases of sludge co-composting. It has been verified that during co-composting there is a potential for reduction of the content of pharmaceutical in the substrates up to 90 %. The course of the temperature in the thermophilic phase is decisive. Growth and ecotoxicity experiments demonstrated that with a suitable co-composting procedure, the resulting stabilized matter is suitable as a substrate for use in plant production, and the risk of using sewage sludge on agricultural land is substantially reduced.
Keywords: léčivé přípravky; kompostování; Agricultural waste; Micropollutants; technologie; Pharmaceuticals; Sewage; Aerobic fermentation; Soil; Plastics; půda; odpadní vody; Composting; Pharmaceutical Preparations; Sewage sludge; plastické hmoty; Technology